Pull Out Tension Capacity of Self Compacting Concrete Containing Rice Husk Ash - Ramlan , Mohd Affendi (Universiti Teknologi Petronas, 2008)
Self-compacting concrete (SCC) is a relatively new kind of high performance concrete product that sees the addition of superplasticiser and a stabilizer to the concrete mix to significantly increase the ease and rate of flow. By its very nature, self-compacting concrete (SCC) does not require vibration. It achieves compaction into every part of the mould or formwork simply by means of its own weight without any segregation of the coarse aggregate. For normal high strength concrete, bonding between concrete and rebar can be considered relatively high due to vibration process. The study related to the shear bond properties of self-compacting concrete and rebar. In additional, the self-compactingconcrete added with admixture namely rice husk ash (RHA). Incidentally, this study focused on the performance of self-compacting-concrete with rice husk ash (RHA) in different three water-to-cement ratio for finding the optimum value of the ratio. Since this study involves rebar and concrete, the performance measured with pull-out-test. The pullout technique measures quantitatively the in-situ strength of the self-compacting concrete when proper correlations have been made. At the end of this investigation, it is identified the optimum water-to-cement ratio and super plasticizers in self-compacting concrete (SCC) for maximum bonding stress between concrete and rebar. It is also to identify the effect of rice husk ash (RHA) as filler in self-compacting concrete (SCC)